Spiral Groove Bearing Geometry Variation Effect on Left Ventricular Assist Device Impeller Performance - Empaling, Shirly; Md Khudzari, Ahmad Zahran; Abdul Kadir, Muhammad Rashidi; Osman, Kahar; Mohamad Hudzari, Akmal Hakim; Padzillah, Mohammad Hasbullah; Abdul Talib, Ishkrizat; Abdul Taib, Mohamed Ezani; Abdul Rahim, Aizai Azan (CFD Letters, 2021)
Mechanical heart assist device has been accepted as a reliable treatment modality for advanced heart failure patient option other than orthotropic heart transplantation. One type of the device is a centrifugal rotary mechanical blood pump that has an impeller levitated using a magnetic motor system in which, it reduces blood damage compared to its predecessors. Spiral Groove Bearing (SGB) is proposed as another design consideration to further decrease blood damage, increasing blood flow in the tight gaps, while maintaining pump performances. There were few studies investigating several aspects of SGB effect on blood flow within the mechanical blood pump, however no study has been done on the SGB geometry configurations, and its effect on device performance. In this study, two design factors of SGB geometry were simulated using computational fluid dynamics (CFD) software – a gap between impeller and housing, and SGB groove depths. The resulting variants were then evaluated using several performance indexes which are pump pressure output, average washout flow, hemolysis index, bearing load carrying capacity and pump efficiency. From the results, there are two conclusions that can be drawn. By deepening SGB groove depth, blood pump performance increased, while increasing the gap between the impeller and pump housing, most performance indexes were reduced. Scoring and screening method was also utilized to evaluate the best variant and it was found that, the variant with SGB groove depths 1000 ?m and gap of 80 ?m was the best in term of overall performances.